Online information seeking patterns and social inequality in a digital economy. - Pekka Räsänen; Aki Koivula; Teo Keipi (Routledge, 2022)
This article aims to map the information-seeking habits of population groups in a digital economy. The growing use of technologies in the modern online era has increased the availability of information regarding services and items through user-generated content and applications. However, the potential for leverage through ICTs may not be evenly distributed across different consumer segments. We use population-level survey data used as the basis for the official statistics in Finland to find differences according to gender, age cohort, education, income and residential area. The results show that Finns are active in using different channels of information acquisition. We found significant differences in how information is obtained between population groups. Men and younger cohorts are more accustomed to using a variety of services and sources for seeking out information. The results also highlighted educational differences that have been rooted in the Finnish information society. Using a nationally representative data, the article points out digital inequalities linked to potential differences in consumer benefits.